Mapping the lymphatic system across body scales and expertise domains: A report from the 2021 National Heart, Lung, and Blood Institute workshop at the Boston Lymphatic Symposium - Singhal, Dhruv; Börner, Katy; Chaikof, Elliot L.; Detmar, Michael; Hollmén, Maija; Iliff, Jeffrey J.; Itkin, Maxim; Makinen, Taija; Oliver, Guillermo; Padera, Timothy P.; Quardokus, Ellen M.; Radtke, Andrea J.; et al. (Frontiers in Physiology, 2023)
Enhancing our understanding of lymphatic anatomy from the microscopic to the anatomical scale is essential to discern how the structure and function of the lymphatic system interacts with different tissues and organs within the body and contributes to health and disease. The knowledge of molecular aspects of the lymphatic network is fundamental to understand the mechanisms of disease progression and prevention. Recent advances in mapping components of the lymphatic system using state of the art single cell technologies, the identification of novel biomarkers, new clinical imaging efforts, and computational tools which attempt to identify connections between these diverse technologies hold the potential to catalyze new strategies to address lymphatic diseases such as lymphedema and lipedema.  This manuscript summarizes current knowledge of the lymphatic system and identifies prevailing challenges and opportunities to advance the field of lymphatic research.